Study of semi-active suspension control strategy based on driving behaviour characteristics. (2015) - Wang, Wenshuo; Xi, Junqiang
In this paper, a semi-active suspension control system incorporating driving behaviour characteristics is presented by recognising driver behaviours on the basis of a quarter car model with a magneto-rheological (MR) damper. First, a specific driver model for recognising driver behaviours is developed to accurately recognise drivers' intentions based on driving data from vehicle sensors. Then, by changing the controllable MR damping ratio in real-time based on the outputs of the driver model, the individual driver's expectation of overall comfort or road-holding performance can be satisfied. Furthermore, simulations of the semi-active suspension control strategy with the driver model compared with the simulations without the driver model are conducted using Matlab/Simulink. The simulation results indicate that the proposed semi-active suspension control strategy with embedded driving behaviour characteristics is better suited to the driver's intentions than other control strategies.